1983
DOI: 10.3171/jns.1983.59.5.0847
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord compression due to prolapse of cervical intervertebral disc (herniation of nucleus pulposus)

Abstract: Twenty-six patients who presented with spinal cord compression due to cervical disc prolapse (herniation of the nucleus pulposus) were treated by anterior discectomy. There was a high incidence of disc prolapse at the C3-4 level. The most severe degrees of preoperative disability were associated with prolapse at that level. Impairment of posterior column function, particularly in the upper limbs, played a major part in producing disability. High cervical disc prolapse can produce a clinical picture that is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 32 publications
1
9
0
3
Order By: Relevance
“…Compressive cervical myelopathy is a disease that can be caused by degenerative spondylosis, ossification of the posterior longitudinal ligament [1,2], intervertebral disc herniation [3], and so on. Patients with compressive cervical myelopathy generally have sensory disturbance in all four limbs, clumsiness in their hands, and spastic gait disturbance due to compression of the cervical spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Compressive cervical myelopathy is a disease that can be caused by degenerative spondylosis, ossification of the posterior longitudinal ligament [1,2], intervertebral disc herniation [3], and so on. Patients with compressive cervical myelopathy generally have sensory disturbance in all four limbs, clumsiness in their hands, and spastic gait disturbance due to compression of the cervical spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…28) Thirty-four of our 134 cases (25.5%) were associated with cervical trauma. Among our patients under 40 years old, 6 of 14 (42.7%) had suffered from cervical trauma.…”
Section: H Ikeda Et Almentioning
confidence: 99%
“…28) Although lumbar disc herniation develops infrequently in teenagers, 13,14) the onset age of cervical disc herniation is comparatively higher. We present a case of nontraumatic cervical disc herniation in a 21-year-old woman, and discuss the pathogenesis of cervical disc herniation in the young.…”
Section: Introductionmentioning
confidence: 99%
“…O'Laoire and Thomas suggested that backward displacement of the cord by a herniated disc is restricted by the posterior rootlets and, because of their attachment adjacent to the cuneate fasciculus, this would lead to distortion of the posterior columns, the cuneate more than the gracile fasciculus. 4 Whatever the underlying mechanism, it is important to recognise this disabling feature of high cervical myelopathy as excision of the disc may bring about a rapid and full recovery.…”
Section: Case Reportmentioning
confidence: 99%